Quantitative analysis of athletic performance enhancement: The effects of aerobic training on VO₂ max in young soccer’s - MARA, Ferdinand; ÇOBAJ, Jorida (Edelweiss Applied Science and Technology, 2025)
Soccer is a high-intensity sport that combines aerobic endurance with agility and neuromuscular coordination to optimize performance. The literature review described the many roles that aerobics play in soccer, from professional performances to youth development, and the range of methods used to evaluate and enhance it. The present study has been designed to examine the impact of incorporating aerobic exercises combined with acrobatic movements into the training regimes of young soccer players and their repercussions on athletic performance as measured by VO₂ Max. A total of 44 male soccer players, aged 18-19, were randomly assigned to either a control group (n = 22), following standard soccer training, or an experimental group (n = 22) that included aerobic and acrobatic exercises three times per week over an entire competitive season. VO₂ Max was measured in the laboratory at the Sports University of Tirana before and after the intervention. Data analysis included independent samples t-tests and Repeated Measures ANOVA. The baseline, control, and experimental groups were statistically not different in their VO₂ Max values. This therefore means that differences at the start did not obscure findings. After training, the experimental group showed a significant increase in VO₂ Max over the control group, thus confirming the hypothesis that the combined aerobic and acrobatic training has positive effects on endurance and athletic performance. There was a significant interaction effect of training modality and VO₂ Max improvement, F (1, 42) = 1176.58, p < .001; the experimental group showed a significantly higher increase in VO₂ Max compared to the control group. These findings indicate that the combination of aerobic and acrobatic exercises in soccer training improves cardiorespiratory endurance and possibly contributes to the general development of an athlete. The study has shown the importance of new training methods in optimizing soccer performance and has provided empirical evidence for their effectiveness. The findings of this study confirm the notion that soccer training programs should combine aerobic drills with acrobatic elements to maximize endurance. Further studies should investigate the long-term effects of such training methods and their influence on match performance and the prevention of injuries.